Low microzooplankton grazing rates in the Arctic Ocean during a Phaeocystis pouchetii bloom (Summer 2007): fact or artifact of the dilution technique? - Calbet, Albert; Saiz, Enric; Almeda, Rodrigo; Movilla, Juan Ignacio; Alcaraz, Miguel (Journal of Plankton Research, 2010)
International audience We studied the structure and dynamics of the microbial community of Arctic waters during July 2007 using a microzooplankton grazing dilution approach. The sampling area covered a latitudinal transect along the East Greenland Sea, and a series of stations in the high Arctic (up to 80º 50' N), west and north of the Svalbard Islands. A main feature of the area was the presence of Phaeocystis pouchetii, which formed dense blooms. Despite the considerable biomass of microzooplankton (mostly large ciliates and dinoflagellates), their grazing impact on phytoplankton was significant only in 6 out of 16 experiments for total chlorophyll a, which resulted in 8% of the standing stock consumed on average. Overall, phytoplankton instantaneous growth rates were very low and even negative at times (range:-0.24 to 0.14; average: -0.04 for total chlorophyll), which could not be attributed to nutrient limitation nor the estimated microzooplankton grazing. We present 3 nonexclusive explanations for this fact: 1) we were facing a senescent community in which many organisms were dying either as a result of virus infections or for other natural causes, as corroborated by parallel estimates of natural cell mortality using membrane permeability probes; 2) the widespread and abundant P. pouchetii was probably deterring grazing and adversely affecting the entire planktonic community at the time of the study; and 3) the dilution technique failed in giving a real estimate of grazing (i.e. either non significant or positive slopes), likely consequence of trophic cascades (decline of major grazers in the more concentrated treatments) combined with saturated-feeding responses.